Factors affecting Palestinian customers' use of online banking services. Issue 2 (14th March 2019) - Salem, Mohammed Z.; Baidoun, Samir; Walsh, Grace
Abstract : Purpose: The purpose of this paper is to examine factors that affect Palestinian customers' use of online banking services. Design/methodology/approach: An empirical study was conducted using a questionnaire in order to test the hypotheses. The questionnaire was distributed to 500 respondents selected by the participating banks. A total of 369 complete questionnaires were returned. The study's independent variables include technology adoption propensity, customers' value for online personalization, customers' privacy concern, e-trust, technological leadership and loyalty. Palestinian customers' usage of online banking services is the dependent variable. Findings: The results of the model tested clearly suggest that the use of online banking services is influenced, respectively, by the technological leadership, e-trust, e-loyalty, customers' value for online personalization, customers' concern for privacy and propensity of technology adoption. Finally, this paper suggests that policy makers should develop a prioritized hierarchy of actions in developing the effective use of bank's online services, based on the t - and p -values of the latter mentioned factors. Research limitations/implications: One limitation of the study is relying on self-reported cross-sectional data collection, rather than longitudinal surveying. Despite such limitation, the study provides the Palestinian banking sector with recommendations to promote online banking services based on the empirically identified factors affecting such service adoption. Practical implications: Palestinian banks should promote the adoption of online banking services by supporting personalization of services, privacy and trust. Customers should always be informed that their bank is among the first banks to introduce the latest state-of-the-art online services. Technology innovative and diverse online services should be offered by banks to attract customers. Originality/value: Although numerous research studies have studied the factors affecting customers in using electronic and online banking services, few studies have considered such usage in the developing countries, such as Arab countries in general and Palestine in particular. This is the first study to examine the factors affecting the adoption of online banking services in Palestine. This study provides empirical evidence to fill in the gap by providing a deeper understanding of the factors affecting the usage of online banking services in the country. The findings of this study can help decision makers in the Palestinian banks to develop practical plans that might accelerate and expand the adoption of online banking emphasizing personalized and trusted services offered with high level of security and privacy.